The Correlation Between Macronutrient And Iron Intake And Cardiorespiratory Fitness Among Rugby Athletes Of UNESA Student Activity Unit - Athaillah Dihyan Wijaya; Desty Muzarofatus Sholikhah (CV. AFDIFAL MAJU BERKAH, 2026)
Cardiorespiratory fitness or VO2 max is an important component in supporting the performance of rugby athletes who require high endurance, but nutritional imbalances are still often found among athletes. This study aims to analyze the relationship between macro nutrient intake and iron intake with physical fitness (cardiorespiratory) among athletes of the Surabaya State University Rugby Club. This study used a quantitative cross-sectional design involving 33 athletes. Macronutrient intake was obtained through a 2x24-hour food recall, iron intake was measured using the Iron-Semi Quantitaive Food Frequency Questionnaire (Iron-SQFFQ), and physical fitness was measured using the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1). The average energy intake of athletes was 2040 ± 457.9 kcal/day, protein 88.3 ± 15.9 g/day, fat 78.2 ± 15.4 g/day, and carbohydrate intake 248.4 ± 75.8 g/day. The average iron intake was 13.7 ± 5.05 mg/day, with most athletes falling into the good category (81.8%). The average VO2 max value of the athletes was 45.0 ± 4.63 ml/kgBW/minute, with the dominant category being sufficient to very good. Data analysis used Spearman's rank correlation test. The correlation test results showed that energy intake (p= 0.008; r=0.451), fat intake (p= 0.004; r= 0.488), and iron intake (p= 0.008; r=0.451) were significantly related significantly with physical fitness, while protein intake (p= 0.133; r=0.267) and carbohydrate intake (p= 0.801; r=0.046) did not show a significant relationship. It was concluded that adequate energy, fat, and iron intake are related to the cardiorespiratory fitness of rugby athletes.